Immersive 3D geovisualizations of geosites in different scales. Combining high-resolution UAV data with a Virtual Reality environment - Papakonstantinou, Apostolos; Papadopoulou, Ermioni - Eirini; Karaelefteriou, Elefterios (My University, 2024)
Immersive 3D geovisualizations offer unprecedented opportunities for experiencing and exploring geosites, providing a powerful tool for conveying a geoheritage site's history and significance to diverse audiences. This study explores the integration of high-resolution unmanned aerial vehicle data with virtual reality environments to create immersive experiences in geosites and, more specifically, at Plaka’s park in Sigrion on Lesvos Island, Greece. UAV scale-variant flight planning techniques were used to ensure that drone data acquisition has the correct spatial resolution based on a 1:50 cartographic scale. Additionally, terrestrial image acquisition was implemented to map the fossil sites on a cartographic scale of 1:5. Furthermore, terrestrial 360 panoramas were captured to enhance the immersive environment and the user experience. The data were processed to generate detailed 3D models of the sites and the fossilized tree trunks. The produced 3D models are integrated into a VR environment to create immersive user experiences. Through VR, users can explore the geosites fully interactively, gaining insights into their significance, unique placement, and fossil details. Integrating high-resolution UAVs with terrestrial data enhances the visual fidelity and realism of the VR experience, allowing users to navigate to the geosites with unprecedented detail and accuracy.
Keywords: 3D geovisualizations; UAV; Virtual Reality (VR); Geosites; Immersive environment